2013
DOI: 10.12775/llp.2013.001
|View full text |Cite
|
Sign up to set email alerts
|

Negation in weak positional calculi

Abstract: Abstract. Four weak positional calculi are constructed and examined. They refer to the use of the connective of negation within the scope of the positional connective "R" of realization. The connective of negation may be fully classical, partially analogical or independent from the classical, truthfunctional negation. It has been also proved that the strongest system, containing fully classical connective of negation, is deductively equivalent to the system MR from Jarmużek and Pietruszczak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The system MR has been presented and examined by Tomasz Jarmużek and Andrzej Pietruszczak (2004), further examined by Marcin Tkaczyk (2013), by Jarmużek and Tkaczyk (2015) and by Anna Maria Karczewska (2018). It has been originally axiomatized by Jarmużek and Pietraszak (2004)…”
Section: The System Mrmentioning
confidence: 99%
See 2 more Smart Citations
“…The system MR has been presented and examined by Tomasz Jarmużek and Andrzej Pietruszczak (2004), further examined by Marcin Tkaczyk (2013), by Jarmużek and Tkaczyk (2015) and by Anna Maria Karczewska (2018). It has been originally axiomatized by Jarmużek and Pietraszak (2004)…”
Section: The System Mrmentioning
confidence: 99%
“…and the system thus constructed is exactly equal to the original version of MR (TKACZYK 2009(TKACZYK , 2013. This information may turn out to be of some use in analyses to come.…”
Section: The System Mrmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative semantic structures, as well as different axiomatizations of the system MR have been defined and examined in [8] and [3]. In particular, it has been shown that the semantics presented here may be generalized, without affecting the set of formulas true in a model, to the cases in which the interpretation of quasi-formulas in positions non denoted by constants from IN need not behave classically [3, pp.…”
Section: Theorem 2 ([2 Pp 155-159]) For All X ⊆ L and A ∈ Lmentioning
confidence: 99%
“…The authors might be treated as continuers of Łoś's approach as series of their articles show: [2,3,4,13,14]. But there are also others logicians who find subject of propositional logic interesting (for example, [7,8,9,10]).…”
mentioning
confidence: 99%